2015
DOI: 10.1111/hir.12125
|View full text |Cite
|
Sign up to set email alerts
|

International trends in health science librarianship part 17: a comparison of health science libraries with academic and research libraries

Abstract: Over the last 4 years this Regular Feature has looked at trends in health science librarianship in the 21st century. Although there are still a few more regions to be covered in this series, this issue explores general trends in academic and research libraries with a view to discovering whether the trends identified for health science libraries are similar. Are health science libraries unique? Or do their experiences mirror those found in the wider world of academic and research libraries? JM

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Last but not least, the article by Murphy from ‘International Perspectives and Initiatives’ explores general trends in academic and research libraries and compares them to the trends identified for health science libraries through the feature's previous 4 years. She concludes that nearly all the top trends reported by health science librarians mapped to those identified by academic librarians, but with some key differences.…”
mentioning
confidence: 99%
“…Last but not least, the article by Murphy from ‘International Perspectives and Initiatives’ explores general trends in academic and research libraries and compares them to the trends identified for health science libraries through the feature's previous 4 years. She concludes that nearly all the top trends reported by health science librarians mapped to those identified by academic librarians, but with some key differences.…”
mentioning
confidence: 99%